Mapping research landscape of emerging technology in the accounting field: a bibliometric analysis - Indrayani; Eko Ganis Sukoharsono; Ali Djamhuri; Roekhudin (Cogent Business & Management, 2024)
This study aims to trace the evolution of research on emerging technologies in the accounting field, map the clustering of this research and identify gaps that require further investigation. Data were collected from Scopus and filtered based on specific criteria, resulting in a final dataset of 324 articles analyzed bibliometrically over the past twenty-eight years. The research method was conducted in two stages: bibliometric analysis and analysis discussion of relevant articles. This study successfully maps emerging technologies in the accounting field into four main clusters, focusing on five key technologies: automation and robotic process automation, artificial intelligence, big data, blockchain and cloud computing. The basic theory or reasoning used by the author to divide the accounting field into four clusters is based on the technology acceptance model. Cluster 1 is technology acceptance and use in the accounting field. Cluster 2 is leveraging technology in the transformation of accounting education. Cluster 3 is implementing technology and innovation in the accounting Profession. Cluster 4 is research and methodology in technology-related accounting studies. This research provides valuable insights for future research agendas. Additionally, the results highlight gaps in the study of emerging technologies within the accounting field, identifying areas that require further exploration.
Keywords: 650; Emerging technologies; bibliometric; accounting field; digital accounting; research